Theoretical Analysis and Experimental Evaluation of Road Dynamic Behavior on Different Subgrades - Xiaoxia Zhao; Jun Wang; Guangya Ding (Advances in Civil Engineering)
The dynamic characteristics of a road on a subgrade filled with different materials under traffic loads are studied. An elastic double-layer plate model on a viscoelastic subgrade is established to describe the dynamic behavior of the road. The load diffusion path in the form of a cone in the stabilised layer under single vibration source and three vibration sources is considered, and the equations for the displacement and effective soil pressure of the elastic double-layer plate on the viscoelastic subgrade are derived. The relevant empirical formulae are then properly revised to reflect the dynamic behavior of the road. The dynamic response of the road is analysed by adjusting factors such as the excitation load, excitation frequency, and subgrade filling materials. The results show that gravel as a subgrade filling material has a better vibration reduction effect than sand bag. In addition, the test data not only have good consistency with the theoretical formulae but also validate the reliability of the empirical formulae.